Uji Aktivitas Antihiperlipidemia Ekstrak Etil Asetat Daun Jambu Air (Syzygium aqueum) terhadap Kadar Kolesterol Total pada Tikus Jantan Galur Wistar - Setianingsih, Siti; Sumantri, Sumantri; ‘Afiah, Noni Faridatul (Journal of Pharmaceutical and Sciences, 2024)
The ethyl acetate extract of guava leaves contains secondary metabolites in the form of flavonoids and alcaloids which have been shown to have an antiperlipidemic. This study aims to determine the content and levels of the ethyl acetate extract of water guava leaves (EEADJA) and antihyperlipidemic activity in hyperlipidemic rats.This research was an experimental study with a randomized matched pre-test and post-test control group design . Hyperlipidemic rats were made by giving PTU 12.5 mg/kg/day orally for 14 days. Hyperlipidemic rats were divided into 5 groups with 5 rats each, namely group I (negative control) CMC-Na 0.5%, group II (positive control) simvastatin 0.18 mg/kgBW/day, groups III, IV and V given EEADJA (100, 200, and 400) mg/kgBW/day for 14 days orally. Differences in data on total cholesterol levels before and after treatment were tested statistically by testing the antihyperlipiemia effect using the paired t-test and One Way Anova test to determine differences in the reduction in total cholesterol levels with various dose variations. EEADJA with various doses of 100, 200, and 400 mg/kg/day has the ability to reduce total cholesterol levels in the blood of hyperlipidemic rats.